Urinary neutrophil gelatinase associated lipocalin as an early marker of acute kidney injury in the recipient after liver transplantation - Hazem El-Akabawy; Mohamed Shafee; Amin Mohamed Roshdy; Ahmed Abd Al Salam (Egyptian Journal of Critical Care Medicine, 2017)
Background: Urinary NGAL is a novel biomarker that is rapidly released after AKI. Purpose: To study the value of urinary NGAL/creatinine ratio in predicting AKI in the recipient of LDLT. Methods: A total of 30 recipients of LDLT were included in a prospective, randomized, two center study. All patients were subjected to a measurement of urinary NGAL/creatinine ratio and the serum creatinine at fashioned time intervals to assess which can predict early renal impairment; accordingly, these data were applied on mortality and hospital stay. Results: Urinary NGAL/creatinine ratio was significant in detecting renal impairment as early as 3, 18, and 24 h post induction of anesthesia (p = 0.001 for all), while it was not significant preoperatively (p = 0.817). Serum creatinine was not significant during the 1st and 2nd days (p = 0.748 and 0.157 respectively), but began to be significant during the 3rd and 4th days (p < 0.001 for both). Urinary NGAL/creatinine ratio was correlated with ICU stay (r = 0.758 with p < 0.001) and mortality during 3, 18, and 24 h postoperative (p < 0.001, <0.001 and 0.005 respectively). The most sensitive in detecting mortality was urinary NGAL/creatinine ratio after 3 h of the operation with a sensitivity of 100% and a specificity of 95.5%. Conclusion: Urinary NGAL/creatinine ratio may be used as a test for the early prediction of adverse outcome of LDLT recipient patients at ICU admission.